Rol' i mesto nauki v podgotovke sportsmenov vysokogo klassa - Absaljamov, T. M. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The author shows some mutually exclusive points of view on the practical contribution of the science to the achievement of the maximum sports results and gives reasons why each of them has the right to existence. He comes to the conclusion, that at the presence of so opposite opinions the true, as a rule, is somewhere in the middle. On the one hand, the thesis about "dominance" of the science in sports is denied by examples of a lot of athletes (here it is possible to refer to some American swimmers) which came in elite of world sports directly from clubs in which not only does not conduct any scientific work, but there is no even doctor. At the same time many coaches and athletes in Russia, and abroad would feel the serious difficulties if have suddenly lost the help of physicians and biologists, if have remained without videorecording, regenerative complexes, other means and the methods now including in the practice of training. What the basic ways of the introduction of results of the scientific researches to the practice of sports for today? Some of them are described in the article.